Implementasi Model Pendekatan Beyond Center And Circle Time (Bcct) Sentra Bahan Alam untuk Meningkatkan Kemampuan Kognitif Anak Usia Dini Usia 5-6 Tahun Kelompok B1 di TK IT AZ-Zahra 1 Kabupaten Sukabumi - Ridayanty, Nurlina; Munajat, Asep (utile: Jurnal Kependidikan, 2018)
This research entitled "Implementation of Beyond Center And Circle Time Approach (BCCT) Model of Natural Material Center to Improve Cognitive Ability of Early Childhood Age 5-6 Year Group B1 In TK IT Az-Zahra 1 Sukabumi". This study uses qualitative research with descriptive research method where the data collected in the form of words so as not to emphasize the number, with the subject of research taken as many as 6 children. The data were collected using observation, interview and documentation study techniques to obtain the answers: (1) How is the learning plan of Beyond Center And Circle Time (BCCT) approach model of natural materials of B1 group in TK IT Az-Zahra 1 Sukabumi regency, (2) How is the implementation of the Beyond Center And Circle Time (BCCT) approach model of B1 Natural Materials Center in TK IT Az-Zahra 1 Sukabumi District, and (3) How is the cognitive ability of early child aged 5-6 years during learning process approach Beyond Center And Circle Time (BCCT) center of natural materials in TK IT Az-Zahra 1 sukabumi regency. The results showed that the implementation of the Beyond Center And Circle Time (BCCT) approach model of natural ingredients can improve the cognitive ability of early child aged 5-6 years group B1 in TK IT Az-Zahra 1 Sukabumi district.